Can Low-Cost Online Summer Math Programs Improve Student Preparation for College-Level Math? Evidence From Randomized Experiments at Three Universities. Issue 4 (2nd October 2017) - Chingos, Matthew M.; Griffiths, Rebecca J.; Mulhern, Christine
ABSTRACT: Every year many students enter college without the math preparation needed to succeed in their desired programs of study. Many of these students struggle to catch up, especially those who are required to take remedial math courses before entering college-level math. Increasing the number of students who begin at the appropriate level of math has become an important focus for educators and policymakers. We conducted randomized experiments of low-cost online summer math programs at three universities to test whether this type of intervention can increase access to math preparation, improve placement and enrollment in fall math classes, and improve performance in first-year math courses. Students who received the intervention engaged with the platform, though at relatively low rates, and were more likely to retake the placement test and improve their scores than students in the control group. However, these improved scores did not translate into enrolling in higher level math courses, obtaining more math credits, or improving grades in math-related courses during the first year of college. Thus, providing students access to this online tool did not improve their math skills.